Epistemology in Mulla Shadra’s Philosophy of Al-Hikmah Al-Muta’aliyah: an Analytical Review - Fitriyati, Intan Diana Fitriyati; Supriyanto (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This study aims to analyze and delve into Mulla Shadra’s views on epistemology and how these views are related to the concept of al-Hikmah al-Muta’aliyah. Analytical methods are employed to understand the philosophical arguments put forth by Mulla ShadraThis study showed that Mulla Shadra introduced an epistemology based on the understanding of al-Hikmah al-Muta’aliyah as the highest source of knowledge. He proposed that true knowledge could be attained through spiritual experience and contemplation, which includes self-understanding and the relationship with God. Intuition and revelation also play a crucial role in Mulla Shadra’s epistemology, where he emphasizes the importance of intuitive understanding as a profound source of knowledge